Proteasome inhibition by bortezomib: A left hook and a right punch - Roelofs, Jeroen (Elsevier, 2015)
Bortezomib (a.k.a. as velcade or PS-341) is used in the clinic to treat multiple myeloma (MM) and mantle cell lymphoma (Dou and Zonder, 2014). In addition to the pharmacokinetic properties of the drug, the effectiveness of the bortezomib depends largely on the difference in drug sensitivity of the target (cancer) cells compared with other cells in the body. For bortezomib this is particularly relevant as it targets a protein complex that is essential for life in all cells. Thus, it is of fundamental importance to understand why different cells show different levels of sensitivity to this drug.